2004
DOI: 10.1111/j.0001-5172.2004.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of etomidate, thiopental, and propofol in induction on hypoperfusion–reperfusion phenomenon during laparoscopic cholecystectomy

Abstract: Propofol with antioxidant activity may offer many advantages by scavenging reactive oxygen species and their metabolites in case of anticipated hypoperfusion-reperfusion phenomenon, such as would occur in laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Post-operative examination showed that in etomidate and thiopental groups, AST and ALT levels in 24 hours showed a marked significant increase, but in propofol group no significant change has been marked. [17] Our study showed in that MDA level was higher in etomidate groups than in other groups.…”
Section: T H I O P E N T a L P R O P O F O L E T O M I D A T E I N T supporting
confidence: 43%
See 2 more Smart Citations
“…Post-operative examination showed that in etomidate and thiopental groups, AST and ALT levels in 24 hours showed a marked significant increase, but in propofol group no significant change has been marked. [17] Our study showed in that MDA level was higher in etomidate groups than in other groups.…”
Section: T H I O P E N T a L P R O P O F O L E T O M I D A T E I N T supporting
confidence: 43%
“…Thus, in clinically suitable concentrations, thiopental is stated to repress the neutrophil originated free oxygen radicals significantly. [17] Basu et al found that propofol had an inflammatory response-decreasing effect compared to thiopental in a study in which oxidative stress and inflammatory response after the renal transplantation were examined. [14] However, we did not detect any significant difference between these two groups in our study.…”
Section: T H I O P E N T a L P R O P O F O L E T O M I D A T E I N T mentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 This is particularly important for inhalation anesthetics because their transformation to reactive products is enhanced by hypoxia and I/R injury. 17,18 After hypoxia and I/R injury, ROS are released to rapid increase of the oxygen concentration in blood via reperfusion of the tissue. 10 In consequence, increased generation of ROS initiates chain reactions such as peroxidation of lipids and of nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has got a preventive role as it scavenges reactive oxygen species and their metabolites in case of anticipated hypoperfusion-reperfusion phenomenon, which occurs in laparoscopic surgery. 5 Thus, propofol appears to be an ideal induction agent for laparoscopic surgeries in ASA I and II patients, but, this vasodilator and down regulation of baroreceptor effect of propofol is markedly pronounced in ASA III elderly, hypertensive patients as the baroreceptor reflex are set at higher level in hypertensives. 6 Fall of mean arterial pressure, if more than 30% may jeopardize coronary circulation.…”
mentioning
confidence: 99%